ABU-ALI IBN SINA ON THE BENEFIT OF PHYSICAL EXERCISE IN THE LIFE OF SOCIETY - Zarofat Igamberdiyevna Yuldasheva; Mahfuza Igamberdiyevna Rahmatullayeva (Proximus Journal Publishing, 2024)
The article is devoted to the contribution of the famous philosopher, thinker, physician and naturalist Abu Ali Hussein ibn Abdullah ibn Sina (Europeanized name Avicenna) to the theory of physical education. The article, based on the analysis of the fundamental work "Canon of Medical Science", shows Ibn Sina's approach to the classification of physical exercises, which act in his theoretical legacy as a means of diagnosing a person's physical condition, a means of developing his physical strength, preserving and improving health, as well as a means of self-regulation while satisfying human vital needs. The authors of the article propose a system of criteria for the classification of physical exercises, highlighted by Ibn Sina. According to the criterion "the amount of physical activity", a block is allocated, which includes "small and large", "strong and weak", "sluggish" physical exercises. According to the criterion "development of certain physical qualities", "fast", "smooth" and "light" physical exercises are distinguished, which correspond to the modern group of speed and strength exercises. Anatomically, there are "chest exercises", "exercises for the digestive organs", "exercises of vision" and "exercises of hearing", "exercises for teeth and ears". The characteristic of the types of physical activity, which is the essence of each typological group of physical exercises, is given. The article presents the requirements that Ibn Sina puts forward for the organization of physical exercises, their intensity, time, age and physical condition of a person. It is concluded that the classification of Ibn Sina's system of physical exercises is internally interfaced with modern classifications of physical exercises, as well as with his own classification and nomenclature of diseases, the description of each of which is accompanied by a recommendation on their use or refusal to exercise
Keywords: Arabic culture; physical culture; Ibn Sina